2021
DOI: 10.3390/biomedicines9030283
|View full text |Cite
|
Sign up to set email alerts
|

Sea Anemone Kunitz-Type Peptides Demonstrate Neuroprotective Activity in the 6-Hydroxydopamine Induced Neurotoxicity Model

Abstract: Kunitz-type peptides from venomous animals have been known to inhibit different proteinases and also to modulate ion channels and receptors, demonstrating analgesic, anti-inflammatory, anti-histamine and many other biological activities. At present, there is evidence of their neuroprotective effects. We have studied eight Kunitz-type peptides of the sea anemone Heteractis crispa to find molecules with cytoprotective activity in the 6-OHDA-induced neurotoxicity model on neuroblastoma Neuro-2a cells. It has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…The yield of the recombinant HCRG21 was 8.2 mg/L cell culture (OD A600 = 0.8). The measured molecular weight of peptide was 6228.5 Da, which corresponded to the calculated data and earlier published results [13,17]. According to the 1 H NMR spectrum the peptide had a well-defined fold.…”
Section: Recombinant Peptide Productionsupporting
confidence: 87%
See 1 more Smart Citation
“…The yield of the recombinant HCRG21 was 8.2 mg/L cell culture (OD A600 = 0.8). The measured molecular weight of peptide was 6228.5 Da, which corresponded to the calculated data and earlier published results [13,17]. According to the 1 H NMR spectrum the peptide had a well-defined fold.…”
Section: Recombinant Peptide Productionsupporting
confidence: 87%
“…It is the first peptide blocker of this channel (inhibits up to 95% of the currents, IC 50 6.9 µM) [13] and has a prolonged analgesic effect (up to 13 h) in the model of thermal pain stimulation [14]. We previously demonstrated that HCRG21 was able to suppress the synthesis of reactive oxygen species in nerve cells and increased their survival in a model of 6-hydroxydopamine-induced neurotoxicity that imitates in vitro Parkinson's disease tightly associated with neuroinflammation [17]. In this study, the potential of HCRG21 was revealed as an effective anti-inflammatory compound.…”
Section: Discussionmentioning
confidence: 99%
“…The peptides have an approximately equal content of secondary structural elements, while a slight increase in α-helixes and decrease in β-structure were found in HCIQ1c9 (Table 1), which might be reflected in the spatial structure and biological activity of the peptide. A comparison of peptide structures with the Kunitz-type peptides InhVJ from H. crispa [44] and SHPI-1 from S. helianthus [53], revealed similar values of secondary structural elements.…”
Section: Calculation Of the Peptides' Secondary Structuresmentioning
confidence: 88%
“…The presence of mutations in Kunitz-type peptides does not affect the spatial molecule structure but leads to the appearance of diverse biological activities toward various targets [39][40][41][42]. Recently, we demonstrated that Kunitz-type peptides of the sea anemone Heteractis crispa inhibit neuroblastoma cell death induced by 6-OHDA via ROS production reductions or antiradical activity [43,44]. Furthermore, some of them demonstrated anti-inflammatory, antihistamine, and analgesic activities [45][46][47][48][49][50], which might also facilitate decreases in both inflammatory and oxidative stress processes inside neuronal cells.…”
Section: Introductionmentioning
confidence: 99%
“…In the sequence of these peptide toxins, the Kunitz motif is a cysteine-rich peptide chain of ~60 amino acid residues with an alpha and beta fold, stabilized by three conserved disulfide bridges [26]. Kunitztype peptides are not only found in sea anemones, but also snakes, spiders, scorpions, and cone snails [27]. They show diverse biological activities, such as inhibition of proteases and/or blocking or modulating ion channels [26].…”
Section: Introductionmentioning
confidence: 99%